Bis-chelate nickel(II) complex with a 1, 5-diaza-3, 7-diphosphacyclooctane ligand: Solid-state structure and redox properties. (27th May 2019) - Khrizanforova, Vera V.; Fayzullin, Robert R.; Strekalova, Sofia O.; Karasik, Andrey A.; Budnikova, Yulia H.
Abstract: The solid-state structure and redox properties of bis-chelate dibromide nickel(II) complex (1 ) with a 1, 5-diaza-3, 7-diphosphacyclooctane ligand (P Ph 2 N Bn 2 ) was reported. Graphical Abstract: UF0001